Remembering Cold Days: The 1942 Massacre of Novi Sad and Hungarian Politics and Society, 1942–1989 - Klimó, Árpád von (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2023)
“Remembering Cold Days” is a book on the changing meanings of the 1942 massacre of Novi Sad. It answers questions about what we know and do not know about this specific war crime today and, most of all, how different individuals and communities have been remembering and interpreting the events since 1942. It also focuses on the changing international context – the massacre was one of hundreds of similar war crimes that marked World War II as one of the worst conflicts for civilians – and the various political regimes which altered the framework for these memories and interpretations. It further looks at a series of trials related to the massacre and the public debates in Hungary, Yugoslavia and elsewhere instigated by a popular novel and film since the mid-1960s. Finally, it analyzes how the end of communism in 1989 and the Yugoslavian wars of the 1990s changed the perspectives on the perpetrators and victims of 1942.